Evaluation of the International Health Regulations core capacities at designated points of entry in Liberia, December 2019 - Siatta Leemu Alberta Gray; Tolbert Geewleh Nyenswah; Julius Saye Miator Gilayeneh Sr; Maame Amo-Addae; Himiede Wede Sesay; Obafemi Joseph Babalola; Philip Kerkula Bemah; Chukwuma David Umeokonkwo (Journal of Interventional Epidemiology and Public Health)
Introduction: In 2014, Ebola Virus Disease (EVD) outbreak struck West Africa, leaving Liberia as the most affected nation. Two years later, a Joint External Evaluation (JEE) conducted in Liberia revealed gaps within the disease surveillance system. These gaps existed due to limited implementation of the International Health Regulation (IHR) 2005 which was adopted by Liberia in 2007. The IHR 2005 is a legally binding document which guides nations to ensure global public health security, with the establishment of minimum core capacities at ports of entry (PoEs) as a requirement to reduce the risk of disease spread. We evaluated the core capacities at eight designated ports of entry in Liberia to assess the implementation of the IHR 2005, measure progress, and set benchmarks for future interventions.